Extended Continental Shelf Under UNCLOS 1982: A Comprehensive Analysis of State Submissions - Taftazani, Muhammad Iqbal; Arsana, I Made Andi; Widjajanti, Nurrohmat; Schofield, Clive (Department of Urban and Regional Planning, Diponegoro University, 2025)
The United Nations Convention on the Law of the Sea (UNCLOS) establishes a framework for coastal states to confirm their continental shelf beyond 200 nautical miles from baselines, often referred to as the Extended Continental Shelf (ECS). This procedure, outlined in UNCLOS Article 76, requires states to submit extensive scientific and legal documentation to the United Nations Commission on the Limits of the Continental Shelf (UN-CLCS). While the technical and legal aspects of ECS delineation have been widely studied, research focused on the process’s broader effects on geospatial governance and marine spatial planning (MSP) is limited. This study aims to examine how the ECS delineation process contributes to geospatial governance and provides a spatial foundation for marine spatial planning. This research addresses this gap by analyzing the executive summaries of 34 successful ECS submissions receiving formal UN-CLCS recommendations. Using qualitative content analysis, the study examines specific criteria states have employed, including their survey methods, data sources, and how they applied UNCLOS formulas and constraints. The data include bathymetric, geophysical, geological, and sediment thickness information from national and international sources. The findings show that bathymetric surveys are used in all submissions, with many states also applying both the Gardiner and Hedberg formulas while consistently adhering to the 350-nautical-mile and 100-nautical-mile-beyond-2,500-m-isobath constraints. The study also highlights the key role of current and former UN-CLCS members in providing expert advice to ensure submissions are scientifically sound and legally valid. Beyond technical aspects, the ECS submission process improves geospatial clarity, decreases jurisdictional uncertainty, and supports sustainable ocean governance.